Neurologic Features of Wolfram Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Nice, Marseille, and Montpellier-Nimes, France, studied the nature and frequency of neurologic manifestations in 59 patients with Wolfram syndrome with genotype-phenotype correlations.